The endocrine effects of nicotine and cigarette smoke - Tweed, Jesse Oliver (2012)
With a current prevalence of approximately 20%, smoking continues to impact negatively upon health. Tobacco or nicotine use influences the endocrine system, with important clinical implications. In this review we critically evaluate the literature concerning the impact of nicotine as well as tobacco use on several parameters of the endocrine system and on glucose and lipid homeostasis. Emphasis is on the effect of smoking on diabetes mellitus and obesity and the consequences of smoking cessation on these disorders. Understanding the effects of nicotine and cigarettes on the endocrine system and how these changes contribute to the pathogenesis of various endocrine diseases will allow for targeted therapies and more effective approaches for smoking cessation.